The increasing prevalence of autism spectrum disorders - Matson, Johnny L.; Kozlowski, Alison M. (Research in autism spectrum disorders, 2011)
Undoubtedly, one of the most frequently studied conditions in the field of mental health today is the autism spectrum disorders (ASD). One of the most controversial topics with respect to this population is the prevalence of this spectrum of disorders. The number of cases has risen dramatically, and various hypotheses have been put forward to explain this phenomenon. Among the most frequently addressed possibilities are expanded diagnostic criteria, more awareness of the disorder, diagnosis at earlier ages, and the recognition that ASD is a lifelong condition. The current paper is a review of the extant literature on this topic. Current status of prevalence research is reviewed and conclusions about the current state of the research are discussed.